Skp2 Inhibitors: Novel Anticancer Strategies - Lee, Yeongju; Lim, Hyun-Suk (Current Medicinal Chemistry, 2016)
Skp2 is frequently overexpressed in many human cancers and plays a key role in tumorigenesis. As a component of the SCFSkp2 ubiquitin E3 ligase complex, Skp2 is responsible for recruiting substrate proteins for their ubiquitination and subsequent degradation by the 26S proteasome. Thus, Skp2 promotes the cell cycle by down-regulating cell cycle proteins such as the tumor suppressor p27. Alternatively, Skp2 suppresses p53-dependent apoptosis by outcompeting p53 for binding to p300, thereby perturbing p300-mediated p53 acetylation and stabilization. Taken together, inhibition of Skp2 functions (either proteolytic function or non-proteolytic function) is emerging as a promising and novel anti-cancer strategy. In the present review, we highlight the development of Skp2 inhibitors with different mechanisms of action.
Keywords: Skp2 inhibitors